Anxious tribalism and the loss of the metanarrative seen in Daniel Everett's mission amongst the Pirahã. Issue 2 (April 2017) - Worsley, Howard John
This article works with the notion of "tribal anxiety" as being a concern over the maintenance of an overarching story and a pressure that causes new identity to emerge. It considers the loss of metanarrative in both the message of the Christian gospel and in its vehicle of universal grammar. The impact of this loss is considered by considering Daniel Everett's encounter with the Pirahã. Anxious tribalism seen in the challenged Christian constructs of Everett is discussed in relation to the larger tribe (the missional perspectives of Everett). The apparent lack of anxious tribalism is discussed in terms of the unchallenged constructs of the smaller tribe (the Pirahã). The linguistic and theological issues arising for missiology are discussed.